Chemical modification of lipases: A powerful tool for activity improvement - Noro, Jennifer Martins (2022)
The demand for adequate and ecologically acceptable procedures to produce the most differentiated products has been growing in recent decades, with enzymes being excellent examples of the advances achieved so far. Lipases are astonishing catalysts with a vast range of applications including the synthesis of esters, flavours, biodiesel, and polymers. The broad specificity of the substrates, as well as the regio-, stereo-, and enantioselectivity, are the differentiating factors of these enzymes. Structural modification is a current approach to enhance the activity of lipases. Chemical modification of lipases to improve catalytic performance is of great interest considering the increasingly broad fields of application. Together with the physical immobilization onto solid supports, different strategies have been developed to produce catalysts with higher activity and stability. In this review, practical insights into the different strategies developed in recent years regarding the modification of lipases are described. For the first time, the impact of the modifications on the activity and stability of lipases, as well as on the biotechnological applications, is fully compiled.